Diel temperature and pH variability scale with depth across diverse coral reef habitats. Issue 2 (20th December 2019) - Cyronak, Tyler; Takeshita, Yuichiro; Courtney, Travis A.; DeCarlo, Eric H.; Eyre, Bradley D.; Kline, David I.; Martz, Todd; Page, Heather; Price, Nichole N.; Smith, Jennifer; Stoltenberg, Laura; Tresguerres, Martin; et al.
Abstract: Coral reefs are facing intensifying stressors, largely due to global increases in seawater temperature and decreases in pH. However, there is extensive environmental variability within coral reef ecosystems, which can impact how organisms respond to global trends. We deployed spatial arrays of autonomous sensors across distinct shallow coral reef habitats to determine patterns of spatiotemporal variability in seawater physicochemical parameters. Temperature and pH were positively correlated over the course of a day due to solar heating and light‐driven metabolism. The mean temporal and spatial ranges of temperature and pH were positively correlated across all sites, with different regimes of variability observed in different reef types. Ultimately, depth was a reliable predictor of the average diel ranges in both seawater temperature and pH. These results demonstrate that there is widespread environmental variability on diel timescales within coral reefs related to water column depth, which needs to be included in assessments of how global change will locally affect reef ecosystems.